Vegetarian, vegan, activist, radical: Using latent profile analysis to examine different forms of support for animal welfare. (September 2019) - Thomas, Emma F.; Bury, Simon M.; Louis, Winnifred R.; Amiot, Catherine E.; Molenberghs, Pascal; Crane, Monique F.; Decety, Jean
There are many different ways that people can express their support for the animals that exist in factory farms. This study draws on insights from the social identity approach, and adopts novel methods (latent profile analysis [LPA]) to examine the qualitatively different subgroups or profiles that comprise broader community positions on this issue. North American participants ( N = 578) completed measures of the frequency with which they engaged in 18 different animal welfare actions. LPA identified 3 meaningful profiles: ambivalent omnivores ( n = 410; people who occasionally limited their consumption of meat/animal products), a lifestyle activist group ( n = 134; limited their consumption of animal/meat products and engaged in political actions), and a vegetarian radical group ( n = 34; strictly limited their consumption of animal/meat products and engaged in both political and radical actions). Membership of the 3 populations was predicted by different balances of social identities (supporter of animal welfare, vegan/vegetarian, solidarity with animals), and markers of politicization and/or radicalization. Results reveal the utility of adopting person-centred methods to study political engagement and extremism generally, and highlight heterogeneity in the ways that people respond to the harms perpetrated against animals.